ANTROPOLOGI SASTRA: ANALISIS HUBUNGAN MANUSIA DENGAN TUHAN DAN SESAMA DALAM NOVEL WESEL POS KARYA RATIH KUMALA - Widiyah; Rahma Annisa; Ahmad Supena (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Examining the significance of human interaction with God and others in the novel Wesel Pos by Ratih Kumala, this research seeks to explain and interpret literary criticism. This research uses a qualitative approach in the form of a text study, examining literary works through the lens of literary anthropology with an emphasis on social and religious context. The novel Wesel Pos is the source of data for this study; excerpts from the book that include social and theological backgrounds are used. The data collection techniques used were reading, listening, noting, and evaluating. Social criticism of human habits and interactions with God and others in social life is found in the novel Wesel Pos. Based on the research findings, the novel Wesel Pos by Ratih Kumala highlights the importance of human relationships with God, specifically believing in God's plan and praying to Him, as well as the importance of human relationships with others, including togetherness, kindness, politeness, love, and cheating.